Technical Efficiencies of Malaysian Commercial Banks: Two Stage Analysis - Singh, G.S, Pritam; S, Munisamy,; Razak Ibrahim, Abdul (Malaysian Journal of Science, 2007)
The purpose of this study is to investigate the efficiency of Malaysian Commercial Banks after the consolidation of the banking system. In this study, the data envelopment analysis (DEA) approach is used to measure the efficiency from 2001 to 2003. Further a Tobit regression is applied to examine the effect of factors that are beyond the control of the management on the bank efficiency. The significant factors are consolidated into the extended DEA model to reflect the true efficiency scores among the banks. The empirical findings indicate a wide diversity of efficiencies from one bank to another and also suggest that the diversity of the resources has had an influence on technical efficiency in Malaysian Commercial Banks.